A Model to Promote University High-Impact Practices Through Community-Based Participatory Research. (September 2022) - Biber, Duke D.; Stoepker, Peter; Gross, Sarah; Heidorn, Jennifer; Brandenburg, Gina; Kay, Christi; Meyer, Adria
There has been a shift in higher education from traditional lecture-based learning to incorporating high-impact practices and experiential learning. These practices offer students an opportunity to engage in real-world settings that allow them to apply course content directly into practice. In order for high-impact practices to be effective, both program implementation and evaluation should be conducted collaboratively with community stakeholders, also known as community-based participatory research (CBPR). The Girls Empowering Movement (GEM) initiative, an out-of-school time physical activity program, is an example of CBPR in that it was developed by middle school girls, for middle school girls. The purpose of this article is to provide the framework used to recruit and train undergraduate students to collaboratively lead the GEM initiative in the southeastern United States. This article discusses how community partnerships were created, how specific content and curricular decisions were made to foster a unique learning experience, and how evaluation protocols were created to ensure undergraduate learning and community collaboration.